Effect of seminal plasma removal, washing solutions, and centrifugation regimes on boer goat semen cryopreservation - Soe, Win Naing; Haron, Abd Wahid; Goriman Khan, Mohd Azam Khan; Yusoff, Rosnina; Abu Bakar @ Zakaria, Md Zuki; Sarsaifi, Kazhal; Bukar, Muhammad Modu; Thein, Myint; Kyaw, Than; San, Maung Maung (Universiti Putra Malaysia Press, 2011)
Three experiments were carried out to improve semen quality during cryopreservation process. Total motility, forward motility, acrosome integrity, live spermatozoa, and normal spermatozoa were measured as semen quality. In Experiment 1, the effects of seminal plasma removal were analyzed by using two different extenders (GE and FE). The removal of seminal plasma gave higher and significant (P<0.05) effect in the total motility, forward motility, and live spermatozoa after cryopreservation. For two different extenders, however, the differences were not observed on the semen quality. In Experiment 2, three different washing solutions (namely, phosphate buffered saline, normal saline and Tris-based extender) were tested to evaluate the effects of semen quality after cryopreservation. Tris-based extender (TCG) conferred the highest (P<.05) sperm quality values in the total motility, forward motility, and live spermatozoa after cryopreservation. In Experiment 3, the effects of different centrifugation regimes (3000 × g for 3 min, 1600 × g for 10 min, 800 × g for 15 min) were evaluated on Boer semen quality. Semen quality parameters (namely, total motility, forward motility, acrosome integrity, and live spermatozoa) were significantly (P<.05) higher for cryopreserved spermatozoa centrifuged with 3000 × g for 3 min than the others. In conclusion, the removal of seminal plasma, washing solution TCG, and the use short-term centrifugation with a relative high g-force could contribute to the increased Boer semen quality after cryopreservation.